2004
DOI: 10.1120/jacmp.v5i2.1966
|View full text |Cite
|
Sign up to set email alerts
|

Surface buildup dose dependence on photon field delivery technique for IMRT

Abstract: The more complex delivery techniques required for implementation of intensity‐modulated radiotherapy (IMRT) based on inverse planning optimization have changed the relationship between dose at depth and dose at buildup regions near the surface. Surface buildup dose is dependent on electron contamination primarily from the unblocked view of the flattening filter and secondarily from air and collimation systems. To evaluate the impact of beam segmentation on buildup dose, measurements were performed with 10×10 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 26 publications
(27 reference statements)
1
0
0
Order By: Relevance
“…These results are consistent with those of previous studies using radiochromic films, ionization chambers, and diodes [40,41]. The energy spectrum, electron contamination from collimator assembly and air, and lateral scattering falling off in FFF photon beams are the reasons behind the variations in the surface doses with field sizes [42,43]. It can be seen from figure 9 that for small field sizes of 0.6 cm×0.6 cm to 6 cm×6 cm, the SNC125c showed the highest value for D S , whereas the lowest value was obtained with the EBT3.…”
Section: Discussionsupporting
confidence: 91%
“…These results are consistent with those of previous studies using radiochromic films, ionization chambers, and diodes [40,41]. The energy spectrum, electron contamination from collimator assembly and air, and lateral scattering falling off in FFF photon beams are the reasons behind the variations in the surface doses with field sizes [42,43]. It can be seen from figure 9 that for small field sizes of 0.6 cm×0.6 cm to 6 cm×6 cm, the SNC125c showed the highest value for D S , whereas the lowest value was obtained with the EBT3.…”
Section: Discussionsupporting
confidence: 91%
“…Technological advances in radiotherapy offer increasingly conformal dose distribution, leading to a steeper dose fall-off outside target volumes (TVs) and resulting in decreased radiation doses to organs at risk (OARs) while maintaining or improving target coverage [4][5][6][7]. Inversely, erroneous segmentation of TVs could potentially cancel the advantage of increased conformity due to unwanted dose deposition in OARs, resulting in a surplus of toxicity and decreased local control [6].…”
Section: Introductionmentioning
confidence: 99%
“…Therapy field accessories such as trays and wedges [7][8][9] and oblique incidence of the beam [10] also affect the surface dose. Lee et al [11] reported surface buildup dose measurements for IMRT that included effects of the patient mask material and oblique incidence [12].…”
Section: Introductionmentioning
confidence: 99%